2009
DOI: 10.1007/s10295-009-0543-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abrasion on biofilm detachment: evidence for stratification of the biofilm

Abstract: The objective of this paper was to understand the detachment of multispecies biofilm caused by abrasion. By submitting a biofilm to different abrasion strengths (collision of particles), stratification of biofilm cohesion could be highlighted and related to stratification of biofilm bacterial communities using the PCR-SSCP fingerprint method. The biofilm comprised a thick top layer, weakly cohesive and composed of one dominant species, and a thin basal layer, strongly cohesive and composed of a more diverse po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
1
21
1
2
Order By: Relevance
“…Las biopelículas microbianas están conformadas por diferentes estratos, cada uno con complejas agrupaciones (Rochex et al, 2009); donde microorganismos pueden ocupar regiones específicas condicionando la estructura de la biopelícula (Tian et al, 2016); además, la estatura y composición de una biopelícula cambia a lo largo del tiempo impulsada por cambios ambientales, disponibilidad de nutrientes y factores intrínsecos a las biopelículas (Ribas et al, 2009;Luria et al, 2016).…”
Section: Discussionunclassified
“…Las biopelículas microbianas están conformadas por diferentes estratos, cada uno con complejas agrupaciones (Rochex et al, 2009); donde microorganismos pueden ocupar regiones específicas condicionando la estructura de la biopelícula (Tian et al, 2016); además, la estatura y composición de una biopelícula cambia a lo largo del tiempo impulsada por cambios ambientales, disponibilidad de nutrientes y factores intrínsecos a las biopelículas (Ribas et al, 2009;Luria et al, 2016).…”
Section: Discussionunclassified
“…We therefore limit ourselves to n ≥ 1, m ≥ 0. The physical mechanisms by which the s-dependence arises are unclear, though potential explanations may involve biofilm stratification with greater cohesiveness towards the base [7,18], or the size distribution of particles detached from the biofilm [cf. 20].…”
Section: The Influence Of Biofilm Detachmentmentioning
confidence: 99%
“…Individual bacteria employ somewhat different methods of dispersal, which can be divided into three discrete stages: (a) detachment of cells from the colony; (b) relocation of cells to an alternative site; and (c) reattachment of the cells to a new substrate site (Kaplan, 2010). Rochex et al (2009) found that one dominant species often comprises most of the weakly cohesive, thick top layer of the biofilm; while a more diverse population comprises the strongly cohesive, thin basal layer. These findings suggest that determining species diversity may be an important parameter in understanding detachment and dispersal.…”
Section: Detachment and Dispersalmentioning
confidence: 99%
“…Biofilms in fluidized beds, filters, and particle-laden environments such as surface waters are often subjected to abrasion (Donlan, 2002). Work by Rochex et al (2009) demonstrated that abrasion characteristics, such as particle collision frequency and pressure strongly affect biofilm detachment rates. Experiments by Gjaltema et al (1997) have shown that inter-particle collisions cause an on-going abrasion of the biofilm…”
Section: Erosion Sloughing and Abrasionmentioning
confidence: 99%